Identifying plant-derived antiviral alkaloids as dual inhibitors of SARS-CoV-2 main protease and spike glycoprotein through computational screening - Yamin, Ramsha; Ahmad, Iqra; Khalid, Hira; Perveen, Asia; Abbasi, Sumra Wajid; Nishan, Umar; Sheheryar, Sheheryar; Moura, Arlindo Alencar; Ahmed, Sarfraz; Ullah, Riaz; Ali, Essam A.; Shah, Mohibullah; et al. (Frontiers in Pharmacology, 2024)
The COVID-19 pandemic is currently considered the ninth deadliest, spreading through direct or indirect contact with infected individuals. It has imposed a consistent strain on both the financial and healthcare resources of many countries. To address this challenge, there is a pressing need for the development of new potential therapeutic agents for the treatment of this disease. To identify potential antiviral agents as novel dual inhibitors of SARS-CoV-2, we retrieved 404 alkaloids from twelve selected medicinal antiviral plants and virtually screened against the renowned catalytic sites and favorable interacting residues of two essential proteins of SARS-CoV-2, namely, the main protease and spike glycoprotein. Based on docking scores, twelve metabolites with dual inhibitory potential were subjected to druglikeness, bioactivity scores, and drug-ability analyses.These analyses included the ligand-receptor stability and interactions at the potential active sites of target proteins, which were analyzed and confirmed through molecular-dynamic simulations of the three lead metabolites. We also conducted a detailed binding free-energy analysis of pivotal SARS-CoV-2 protein inhibitors using molecular mechanics techniques to reveal their interaction dynamics and stability. Overall, our results demonstrated that twelve alkaloids, namely adoutine Y, evodiamide C, ergosine, hayatinine, (+)-homoaromoline, isatithioetherins C, N,alpha-Lrhamnopyranosyl vincosamide, pelosine, reserpine, toddalidimerine, toddayanis, and zanthocadinanine, are shortlisted metabolites based on their interactions with target proteins. All twelve lead metabolites exhibited a higher unbound fraction and therefore greater distribution compared to the standards. Particularly, adouetine Y demonstrated high docking scores but exhibited a non-spontaneous binding profile. In contrast, ergosine and evodiamide C showed favorable binding interactions and superior stability in MD simulations. Ergosine demonstrated exceptional performance in several key pharmaceutical metrics. Pharmacokinetic evaluations revealed that ergosine exhibited pronounced bioactivity, good absorption, and optimal bioavailability. Additionally, it was predicted not to cause skin sensitivity and was found to be non-hepatotoxic. Importantly, ergosine and evodiamide C emerged as superior drug candidates for dual inhibition of SARS-CoV-2 due to their strong binding affinity and drug-ability, comparable to known inhibitors like N3 and molnupiravir. The study is limited due to its in-silico nature and demands the need for future in-vitro and in-vivo studies to confirm these findings.